2015
DOI: 10.1016/j.arth.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Perioperative Outcomes of Off-Label Total Hip and Knee Arthroplasty in the United States, 2000–2010

Abstract: “ Off-label use” refers to medical device utilization for purposes or subpopulations other than those approved by the United States Food and Drug Administration. The primary goal of this study was to determine the current epidemiology of off-label total hip and knee arthroplasty (THA and TKA, respectively) in the United States and to project further off-label use through 2040. Over the past decade, the prevalence of off-label THA and TKA was 30.4% and 37.0%, respectively, growing ~70% from 2000 2010. By 2040, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…“Off­label use” refers to use of medical devices for purposes or subpopulations other than those approved by the United States Food and Drug Administration (Malcolm et al. 2015 ). Malcolm et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Off­label use” refers to use of medical devices for purposes or subpopulations other than those approved by the United States Food and Drug Administration (Malcolm et al. 2015 ). Malcolm et al.…”
Section: Discussionmentioning
confidence: 99%
“…Malcolm et al. ( 2015 ) demonstrated that the prevalence of off­label THAs and TKAs was 30% and 37%, respectively, in the USA. They predicted an increase in the prevalence of off-label arthroplasties in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 ] With the aging of the US population, the number of TKR is expected to obviously increase by 2030, reaching estimated 3.48 million a year. [ 3 , 4 ] In the acute stage after surgery, TKR can lead to obvious pain, and the postoperative knee pain has become a familiar and persistent chief complaint after the TKR, leading to patient poor life quality and dissatisfaction. The reported incidence of severe postoperative knee pain after TKR ranges from 10.3% to 36.8%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] In the wake of the aging of the US population, the number of knee arthroplasty is expected to obviously increase by 2030, with the estimated 3.48 million cases each year. [ 3 , 4 ] Although UKA recovers faster than total knee arthroplasty, with better function and fewer complications, it is related to serious postoperative pain. There are many methods for the treatment of the postoperative pain, containing block of femoral nerve, local infiltration anesthesia, and intravenous opioids as well as intrathecal analgesia, [ 5 7 ] the management of pain after the UKA is challenging in orthopedic field.…”
Section: Introductionmentioning
confidence: 99%